Pengaruh Perceived Usefulness Dan Convenience Terhadap Perubahan Perilaku Konsumen OFD Di Indonesia Melalui Hedon Enjoyment - Khairilisani, Destita; Wulandari, Winda (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study uses a quantitative approach to examine the influence of perceived usefulness (PU) and convenience (CV) on behavioral change (BC) among online food delivery (OFD) app users in Indonesia, with hedonistic enjoyment (HE) as a mediating variable. A total of 248 respondents, active users of Gofood, Grabfood, and ShopeeFood, participated in the online survey. Data was analysed by partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The result showed that CV had significant effect on HE (B = 0.541; p < 0.001), while PU had no significant effect. PU, CV, and HE all had a positive effect on BC, with HE being the strongest predictor (B = 0.340 ; p < 0.0001). A mediation test indicated that HE partially mediated the effect of CV on BC, but did not mediate the relationship between PU an BC. These findings provide practical implications for OFD service developers to prioritize convenience and enjoyable experiences in customer acquisition and retention strategies, particularly for younger user segments such as Generation Z.